Sófocles: la lengua de un innovador. 20 años de investigación lingüística (1983-2003) - Jiménez López, María Dolores (Estudios clásicos, 2005)
The present situation of the linguistic research on Sophocles' work is revised due to the comrnemoration of his 25th centenary. The studies in this field in the last twenty years, instead of providing new facts, help us to deepen, qualify or irnprove previous analysis. Therefore, most of these studies go beyond a strictly linguistic research in order to contribute to a better overall understanding of the Sophoclean tragedy.